THE SIGNIFICANCE OF BIOGAS PRODUCTION ON THE AGRICULTURAL FARMS IN VOJVODINA - Jovanović, Milenko; Radaković, Darko; Kiš, Ferenc (Economics of Agriculture, 2008)
All countries of the world deal with problems related to the energy provision and the protection of the environment in a lesser or a greater extent. The consequences of current relations between the production and consumption of electric power are permanent increase in price of the electric power, which leads to the ecologically and economically reasonable necessity to include the alternative sources in the global strategy of energetics development. Since the Republic of Serbia can not act as being isolated from the world processes, she undertook the obligations related to energetics under the Athens Memorandum and the Kyoto Protocol, for the protection and improvement of environment, as well as for the fulfillment of standards for the purpose of further integrations. Biogas in Serbia becomes the alternative source of energy on agricultural households in two aspects – the aspect of energetics and the aspect of ecology. In comparison to techniques of electric power production from other renewable and fossil biogenic energy sources, the usage of biogas from the liquid manure is accomplished with a significant decrease in gas emissions which lead to the hothouse effect.